Checkpoint Inhibition for Metastatic Urothelial Carcinoma After Chemotherapy—Real-World Clinical Impressions and Comparative Review of the Literature - Fuhrmann, Christian; Struck, Julian P.; Ivanyi, Philipp; Kramer, Mario W.; Hupe, Marie C.; Hensen, Bennet; Fürschke, Alexander; Peters, Inga; Merseburger, Axel S.; Kuczyk, Markus A.; von Klot, Christoph-A. J. (Frontiers in Oncology, 2020)
Background: The introduction of checkpoint inhibitors is a long-awaited new option for a urothelial cancer with a poor prognosis. Apart from clinical studies, the data on real world experience is scarce. Methods: Patients for monotherapy with either Atezolizumab, Nivolumab or Pembrolizumab after chemotherapy were included. Adverse events and immune related adverse events as well as survival data and imaging analyses were recorded in a prospectively designed multi-center data base. Duration of response, progression free survival (PFS), and overall survival (OS) were estimated with the Kaplan-Meier method. Results: A total of 28 patients were included. The median follow-up was 8.0 (range, 0.7–41.7) months. Median PFS was 5.8 (95% CI, 2.3–NA) months. Median OS for all patients was 10.0 (95% CI, 8.0–NA) months. The overall response rate (ORR) was 21.4% (6 out of 28 patients). Adverse events were recorded in 20 (71.4%) of patients. Higher grade adverse events (≥Grade 3) were present in 11 (39.3%) patients. No therapy related deaths occurred during the observation period. A total of 13 (46.4%) patients had adverse events that were considered to be immune related. The most commonly affected organ was the thyroid gland with 21.4% of events. Conclusion: Our real-world clinical series confirms an objective response for about every fifth patient, promising OS and a low incidence for severe adverse events (≥Grade 3).